IN-VITRO ANTIOXIDANT ACTIVITY OF PLANT ELAEOCARPUS TUBERCULATUS ROXB. - Mathad, Vikas R.; V., Jayadevaiah K.; R., Vinay; S., Basavaraja H.; R., Bharathi D.; V., Rajashekhar K. (Journal of Biomedical and Pharmaceutical Research, 2019)
A majority of the population in the developing world is struggling to raise living standards and improve health-care delivery due to increasing poverty and population. According to an estimate, 70-80% of the developing world is dependent on conventional plant-obtained remedies, as pharmaceuticals are high priced, so the present study was aimed at evaluating the crude ethanolic extract of stem bark of plant Elaeocarpus tuberculatus Roxb. belonging to the family Elaeocarpaceae with in- vitro antioxidant activity by following various methods namely total reducing power and free radical scavenging activity was evaluated using 1,1-diphenyl-2-picryl hydrazyl (DPPH) free radical. The crude ethanolic extract possesses significant concentration dependent inhibition of DPPH activity and concentration dependent increase in reducing power property against the standard ascorbic acid. Our findings provide evidence that the crude ethanolic extract of stem bark of Elaeocarpus tuberculatus Roxb. is a potential source of natural antioxidant. Keywords: Elaeocarpus tuberculatus Roxb., 1,1-diphenyl-2-picryl hydrazyl (DPPH), Total reducing power, ascorbic acid.